Instructing Young Children in the Use of Memorizing Strategies: Effects at Study and Recall - Pierce, Sarah; Lange, Garrett (The Journal of general psychology, 1993)
This study examined preschool children's abilities to apply a newly learned organizational study-recall strategy in posttraining tasks that employed stimulus items from different media and that were administered by an unfamiliar experimenter. Fortyeight 4- and 5-year-old children were assigned to training and control conditions that alternated the presentation of pictures and objects on baseline, training, and test tasks. Samemedium tasks required children to study and recall items of the same stimulus medium (pictures or objects) as that depicting items in the training tasks. Different-medium tasks required performance with items presented in the alternate medium. Training included demonstration and practice in using a study-sorting strategy to organize the stimuli, encouragement to apply the strategy in new tasks, presenting a rationale for using the strategy, giving feedback about the effectiveness of using the strategy, and providing incentive for effortful performance. Subjects in the training groups showed marked increases in the use of sorting activities in posttraining tasks but failed to show corresponding significant improvements in item recall.